Post-conflict Urban Renewal as an Ethnocratic Regime Practice: Racialized Governance of Redevelopment in Diyarbakir, Turkey - Ay, Deniz; Turker, Kaner Atakan (Frontiers in Sustainable Cities, 2022)
This paper explores the governance of a state-led urban renewal project in a politically contested area in the aftermath of a major armed conflict. Building on the ethnocratic regime theory, we explore the governance of the urban renewal process in the historic district of Suriçi by focusing on the political, spatial, and governmental underpinnings of displacement and dispossession in the context of the unresolved “Kurdish Question” of Turkey. We argue that this exclusionary and state-led urban renewal project is shaped around the ethnocratic state interests with limited real estate returns that aims to sanitize and dehistoricize the historic core of Diyarbakir given its political and socioeconomic significance for the Kurdish Movement. The rhetorical formation of a “renewed” historic core epitomizes the racialized governance that intensifies the race-class realities sitting at the center of the decades-old ethnic conflict in Turkey. The central government authority's use of gentrification in practice illustrates the ethnocratic regime's spatial, political, and economic repercussions for the Kurdish population as the country's largest ethnic minority. Suriçi‘s redevelopment illustrates that ethnocratic regime practices coexist with a democratic façade and militarization activates an ethnocratic urban regime. Our findings contribute to the literature on space and power by illustrating the incompleteness and paradoxical elements of settler-colonial urbanism.